Indicadores de ensino básico brasileiros relativos aos objetivos de desenvolvimento sustentável numa perspectiva internacional comparada - Milko Matijascic; Carolina Esther Kotovicz Rolon (Instituto de Pesquisa Econômica Aplicada (IPEA), 2020)
– This paper aims to illustrate the situation of the basic education in Brazil through an international comparison of the Sustainable Development Goals' (SDGs) indicators. The paper presents 54 SDG 4 indicators on Basic Education for Brazil and thirteen other countries, namely, Argentina, Chile, China, Colombia, Germany, India, Italy, Mexico, Portugal, Russia, South Africa, Sweden ant the USA. The countries were selected according to criterions of geographical proximity to Brazil, territorial and population size and social policy models. All indicators and their values were calculated based on UNESCO's databases and the values are for 2015 or the closest year to 2015 with available data. The criterions to select the indicators were those with values for Brazil and focusing on the goals concerning the Basic Education level (pre-primary, primary and secondary schooling levels).
Keywords: I21; 330; compared educational systems; educational indicators; Sustainable Development Goals